Geometry and Algebra in Ancient Civilizations - van der Waerden, B. L. (1983)
56-63: Babylonian Mathematics; 64- 69: Chinese and Babylonian Algebra Compared; 85-86: Another Concordance Between the Babylonians and Euclid; 158-163: Babylonian, Egyptian and Early Greek Problems; 168-170: Two More Problems of Babylonian Type.